Effect of progesterone on Smad signaling and TGF-β/Smad-regulated genes in lung epithelial cells. - Steffen Kunzmann; Barbara Ottensmeier; Christian P Speer; Markus Fehrholz (PLoS ONE)
The effect of endogenous progesterone and/or exogenous pre- or postnatal progesterone application on lung function of preterm infants is poorly defined. While prenatal progesterone substitution may prevent preterm birth, in vitro and in vivo data suggest a benefit of postnatal progesterone replacement on the incidence and severity of bronchopulmonary dysplasia (BPD). However, the molecular mechanisms responsible for progesterone's effects are undefined. Numerous factors are involved in lung development, airway inflammation, and airway remodeling: the transforming growth factor beta (TGF-β)/mothers against decapentaplegic homolog (Smad) signaling pathway and TGF-β-regulated genes, such as connective tissue growth factor (CTGF), transgelin (TAGLN), and plasminogen activator inhibitor-1 (PAI-1). These processes contribute to the development of BPD. The aim of the present study was to clarify whether progesterone could affect TGF-β1-activated Smad signaling and CTGF/transgelin/PAI-1 expression in lung epithelial cells. The pharmacological effect of progesterone on Smad signaling was investigated using a TGF-β1-inducible luciferase reporter and western blotting analysis of phosphorylated Smad2/3 in A549 lung epithelial cells. The regulation of CTGF, transgelin, and PAI-1 expression by progesterone was studied using a promoter-based luciferase reporter, quantitative real-time PCR, and western blotting in the same cell line. While progesterone alone had no direct effect on Smad signaling in lung epithelial cells, it dose-dependently inhibited TGF-β1-induced Smad3 phosphorylation, as shown by luciferase assays and western blotting analysis. Progesterone also antagonized the TGF-β1/Smad-induced upregulation of CTGF, transgelin, and PAI-1 at the promoter, mRNA, and/or protein levels. The present study highlights possible new molecular mechanisms involving progesterone, including inhibition of TGF-β1-activated Smad signaling and TGF-β1-regulated genes involved in BPD pathogenesis, which are likely to attenuate the development of BPD by inhibiting TGF-β1-mediated airway remodeling. Understanding these mechanisms might help to explain the effects of pre- or postnatal application of progesterone on lung diseases of preterm infants.